Carbon nanotube based transparent conductive films: progress, challenges, and perspectives - Zhou, Ying; Azumi, Reiko (Science and technology of advanced materials, 2016)
Developments in the manufacturing technology of low-cost, high-quality carbon nanotubes (CNTs) are leading to increased industrial applications for this remarkable material. One of the most promising applications, CNT based transparent conductive films (TCFs), are an alternative technology in future electronics to replace traditional TCFs, which use indium tin oxide. Despite significant price competition among various TCFs, CNT-based TCFs have good potential for use in emerging flexible, stretchable and wearable optoelectronics. In this review, we summarize the recent progress in the fabrication, properties, stability and applications of CNT-based TCFs. The challenges of current CNT-based TCFs for industrial use, in comparison with other TCFs, are considered. We also discuss the potential of CNT-based TCFs, and give some possible strategies to reduce the production cost and improve their conductivity and transparency.